2019
DOI: 10.1152/japplphysiol.00917.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training, detraining, and retraining on strength, hypertrophy, and myonuclear number in human skeletal muscle

Abstract: Previously trained mouse muscles acquire strength and volume faster than naïve muscles; it has been suggested that this is related to increased myonuclear density. The present study aimed to determine whether a previously strength-trained leg (mem-leg) would respond better to a period of strength training than a previously untrained leg (con-leg). Nine men and 10 women performed unilateral strength training (T1) for 10 wk, followed by 20 wk of detraining (DT) and a 5-wk bilateral retraining period (T2). Muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 49 publications
(54 reference statements)
3
50
2
Order By: Relevance
“…However, muscle fibre size remained unchanged during detraining as well as 5 weeks of bilateral retraining. Furthermore, no changes in myonuclear content could be detected in response to the initial training, detraining, or retraining period 11 . The degree of muscle fibre growth observed during the initial 10 weeks of exercise training may have been too small to elicit a group mean increase in myonuclear content which is required to firmly establish whether muscle memory by myonuclear retention exists in humans.…”
Section: Evidence From Human Studiesmentioning
confidence: 94%
See 3 more Smart Citations
“…However, muscle fibre size remained unchanged during detraining as well as 5 weeks of bilateral retraining. Furthermore, no changes in myonuclear content could be detected in response to the initial training, detraining, or retraining period 11 . The degree of muscle fibre growth observed during the initial 10 weeks of exercise training may have been too small to elicit a group mean increase in myonuclear content which is required to firmly establish whether muscle memory by myonuclear retention exists in humans.…”
Section: Evidence From Human Studiesmentioning
confidence: 94%
“…Currently there is only one study that attempted to directly test the hypothesis of muscle memory by myonuclear permanence in humans. In the study by Psilander et al, 11 healthy young men performed 10 weeks of unilateral resistance exercise training, followed by 20 weeks of detraining and a subsequent 5 weeks of bilateral retraining. Skeletal muscle thickness and strength increased significantly in response to the initial exercise training period, which was mostly lost during the successive 20 weeks of detraining.…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It should, however, be mentioned that, in experimental models, hypertrophic responses in skeletal muscle have reportedly been observed without myonuclear accretion (Blaauw et al, 2009;McCarthy et al, 2011). Similarly, a recent human study found no increase in myonuclear number that would accompany gains in muscle force and mass in the course of 10 weeks of leg strength training (Psilander et al, 2019). Further complication arises from a recent murine study that reported traininginduced increases in myonuclear density but found no evidence for a retention of these newly recruited myonuclei that would last over a subsequent period of detraining (Dungan et al, 2019).…”
mentioning
confidence: 99%